SUPPORTIVE CLASSROOM CLIMATE AND PUBLIC SPEAKING SELF-EFFICACY AMONG UNDERGRADUATE STUDENTS: A CORRELATIONAL STUDY - Aji Cokro Dewanto; Dwi Ario Fajar; Sattra Sahatsathatsana (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Public speaking is an essential academic skill in higher education, yet many students experience low confidence when speaking in front of an audience. Although classroom climate has been widely examined in relation to motivation and learning outcomes, limited research has specifically investigated supportive classroom climate in relation to public speaking self-efficacy among undergraduate students in the Indonesian higher education context. This study examined the relationship between supportive classroom climate and public speaking self-efficacy among undergraduate students. A correlational research design was employed involving 109 undergraduate students from a private university in Indonesia, selected using a convenience sampling method. Participants completed the Supportive Classroom Climate Scale and the Public Speaking Self-Efficacy Scale. Data were analyzed using Pearson’s correlation and multiple regression analysis. The findings showed that supportive classroom climate was positively associated with public speaking self-efficacy. Among the classroom climate dimensions, lecturer support emerged as the main predictor, whereas peer support and participation climate showed more limited contributions. These findings suggest that supportive instructional environments, particularly encouragement and feedback from lecturers, play an important role in strengthening students’ confidence in academic speaking contexts. Creating supportive classroom environments may therefore help promote students’ engagement and self-efficacy in public speaking activities. ABSTRAK Berbicara di depan umum merupakan keterampilan akademis yang esensial dalam pendidikan tinggi, tetapi banyak mahasiswa masih kurang percaya diri saat berbicara di hadapan audiens. Meskipun iklim kelas telah banyak dikaji dalam kaitannya dengan motivasi dan hasil belajar, penelitian yang secara khusus menguji hubungan antara iklim kelas yang mendukung dan efikasi diri berbicara di depan umum pada konteks mahasiswa Indonesia masih terbatas. Penelitian ini mengkaji hubungan antara iklim kelas yang mendukung dan efikasi diri berbicara di depan umum di kalangan mahasiswa sarjana. Desain penelitian korelasional digunakan dengan melibatkan 109 mahasiswa sarjana dari sebuah universitas swasta di Indonesia, yang dipilih menggunakan metode convenience sampling. Para peserta mengisi Supportive Classroom Climate Scale dan Public Speaking Self-Efficacy Scale. Data dianalisis menggunakan korelasi Pearson dan regresi berganda. Hasil penelitian menunjukkan bahwa iklim kelas yang mendukung berhubungan positif dengan efikasi diri berbicara di depan umum. Di antara dimensi iklim kelas, dukungan dosen muncul sebagai prediktor utama, sedangkan dukungan teman sebaya dan iklim partisipasi menunjukkan kontribusi yang lebih terbatas. Temuan ini menunjukkan bahwa lingkungan pembelajaran yang suportif, khususnya melalui dorongan dan umpan balik dari dosen, berperan penting dalam memperkuat kepercayaan diri mahasiswa dalam konteks berbicara akademis. Oleh karena itu, penciptaan iklim kelas yang mendukung dapat membantu meningkatkan keterlibatan dan efikasi diri mahasiswa dalam kegiatan berbicara di depan umum.